2009
DOI: 10.1007/s11011-009-9151-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sulfatase deficiency: clinical report and description of two novel mutations in a Brazilian patient

Abstract: Multiple Sulfatase Deficiency (MSD) is a rare autosomal recessive disease in which the activities of all sulfatases are reduced; its estimated prevalence is 1:1.4 million births. The disease is caused by mutations in SUMF1, which encodes an enzyme involved in the post-translational modification of sulfatases. The MSD phenotype is a combination of the clinical features found in diseases resulting from a deficiency of the individual sulfatases; i.e., mucopolysaccharidosis II, IIIA, IIID, IVA and VI, metachromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…25 Until now, more than 30 different SUMF1 mutations were found, most of which are missense mutations. 9,23,26,20,27 In a first approach, we investigated the consequences of four different MSD causing SUMF1 mutations on FGE 13 expression, localization, stability and activity in either an overexpressing cell-culture model or in patient fibroblasts. We found that all four variant FGE proteins could be expressed in HT-1080 cells, correctly localizing to the ER.…”
Section: Introductionmentioning
confidence: 99%
“…25 Until now, more than 30 different SUMF1 mutations were found, most of which are missense mutations. 9,23,26,20,27 In a first approach, we investigated the consequences of four different MSD causing SUMF1 mutations on FGE 13 expression, localization, stability and activity in either an overexpressing cell-culture model or in patient fibroblasts. We found that all four variant FGE proteins could be expressed in HT-1080 cells, correctly localizing to the ER.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple Sulfatase Deficiency (MSD, OMIM #272200) is a type of lysosomal storage disorder (LSD) which is inherited through an autosomal recessive (AS) pattern ( 2 , 3 ) that can result in the insufficient activity of all sulfatase family enzymes due to post-translation protein modification defects in which conversion of cysteine into c-αformylglycine in the catalytic domain is disrupted ( 4 , 5 ), thus causing the accumulation of sulfate esters aforementioned ( 2 , 3 ) which results in neurological deterioration and mental delay, organomegaly, skin changes, dysmorphism and skeletal abnormalities ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in the SUMF1 gene (OMIM *607939) encoding sulfatase modifying factor 1 (SUMF1) protein are responsible for post-translation protein defects ( 2 , 4 ). More than 30 mutations in SUMF1 gene have been identified, with the majority of them being missense mutations that can disrupt the stability and activity of formylglycine generating enzyme (FGE).…”
Section: Introductionmentioning
confidence: 99%
“…Die MSD ist eine monogenetische Erkrankung. Bis heute konnten mehr als 30 verschiedene FGE-Mutationen identifiziert werden, wobei es sich insbesondere um missense-Mutationen handelt (Artigalás et al 2009;Cosma et al 2004;Diaz-Font et al 2005;Dierks et al 2003Dierks et al , 2005. Eine Schlüsselrolle im Entstehungsmechanismus der Erkrankung spielt das durch den Gendefekt modifizierte FGE, welches für die Aktivierung neu synthetisierter Sulfatasen im endoplasmatischen Retikulum (ER) essentiell ist.…”
Section: Pathophysiologieunclassified
“…Die Auswahl der in dieser Arbeit untersuchten FGE-Mutationen erfolgte auf der Grundlage von Ergebnissen aus vorherigen Analysen (Artigalás et al 2009;Cosma et al 2003Cosma et al , 2004Diaz-Font et al 2005;Dierks et al 2003, 2005, 2009, Schlotawa et al 2008. Die 8 Anhang (Tabellen und Abbildungen)…”
Section: Produktion Der Fge-mutantenunclassified